Exploring the Drivers of Consumer Online Purchase Behavior - Bajracharya, Sajesh; Thapa, Sikchhya (DAV Research Journal, 2025)
This study examines the effect of different factors, such as perceived benefits, website availability, psychological factors on consumer online buying behavior (COBB) in Nepal. It aims to address gaps in understanding how these factors shape online purchase decisions in Nepal’s emerging e-commerce context. A quantitative survey was conducted among 150 bachelor-level students in the Kathmandu Valley of Nepal using convenience sampling. A causal research design was adopted, and data were collected via a structured Likert-scale questionnaire and analyzed using SPSS with descriptive statistics, correlation, and regression analysis. The results revealed a significant influence of website availability and perceived risk on consumer online buying behavior. Perceived risk and website availability significantly influence online buying behavior in Nepal by fostering trust and ease of use. Convenient access, diverse products, and user-friendly website designs drive consumer confidence and engagement in online shopping. Online retailers in Nepal could collaborate with web developers to enhance website usability and security, creating trustworthy and user-friendly platforms. Such efforts can boost consumer confidence and increase online shopping adoption.